A Translational Paradigm for Univentricular Heart Disease: Single-Stage Neonatal Repair with Adaptive Control of Cavopulmonary Flow - Paulo Cesar Duarte Junior; Martin Poulsen Kessler; Alessandro Cavalcanti Lianza; Shirley Ferraz Crispilho; Rudolf Huebner; Hemerson Donizete Pinheiro; Aron José Pazin de Andrade (Cardiovascular Engineering and Technology, 2026)
Background Univentricular heart defects remain one of the greatest challenges in pediatric cardiovascular surgery. Although well-established, the traditional approach consisting of three serial palliative procedures (Norwood, Glenn, and Fontan) entails cumulative risks, repeated hospitalizations, high healthcare costs, and significant psychosocial impact. This study proposes a single-stage neonatal surgical strategy integrating a tissue-engineered vascular graft and a differential flow control valve to enable adaptive and gradual modulation of cavopulmonary flow, avoiding abrupt physiological transitions. To evaluate the hemodynamic feasibility of the proposed concept, a three-dimensional computational fluid dynamics model was developed and analyzed under controlled flow conditions. Methods A three-dimensional model of the total cavopulmonary connection was developed to evaluate the hemodynamic feasibility of the surgical proposal. The fenestration diameter was reduced from 14 to 0 mm, representing progressive hemodynamic conditions. Computational fluid dynamics simulations were conducted under standardized physiological conditions, with neonatal pulmonary vascular resistance represented by porous zones. Flow distributions, pressure gradients, and hemodynamic equilibrium points were evaluated. Results Progressive reduction of fenestration diameter from 14 to 0 mm promoted gradual redistribution of venous flow from predominant right atrial diversion to predominant pulmonary perfusion. Systemic venous pressure increased from 4.2 to 10.6 mmHg as fenestration diameter decreased. An intermediate functional range between 5 and 6 mm provided a balanced distribution between pulmonary perfusion and right atrial diversion, consistent with an intermediate cavopulmonary flow condition. Conclusion Within the assumptions of this proof-of-concept computational model, the proposed strategy demonstrated hemodynamic feasibility for progressive cavopulmonary flow modulation. By integrating tissue engineering, adaptive flow control, and computational modeling, the proposed concept provides a foundation for future patient-specific, experimental, and translational investigations in the treatment of univentricular heart defects.